Muscular Tuberculosis: A New Case and a Review of the Literature - Zeng, Yanping; Liu, Yin; Xie, Yanchun; Liang, Jingjing; Kuang, Jiabing; Lu, Zuneng; Zhou, Yu (Frontiers in Neurology, 2019)
Objective: To investigate the clinical manifestations, underlying diseases, pathological features, and therapeutic responses in patients with muscular tuberculosis (MT), which is rare and often misdiagnosed in clinical practice. Methods: This study describes a rare MT case that was recently diagnosed in our department. Additionally, 18 other MT cases retrieved from the PubMed database from 2,000 to date are included in this study. The clinical manifestations, areas of residence, underlying diseases, laboratory test results, pathology results, and outcomes of the patients were recorded and analyzed. Results: The MT patients in this study included 13 males and six females with an average age of 34.58 years old. Eight patients were from Asia, and six patients were from Africa, accounting for the majority of patients, at 73.68%. Underlying diseases included flu-like illness in one patient; chronic kidney disease (CKD) in one patient; Sjögren's syndrome in one patient; systemic lupus erythematosus (SLE), lupus nephropathy, and deep vein thrombosis in one patient; and Alzheimer's disease (AD) and Paget's disease in one patient. Two patients had a previous history of tuberculosis, and two patients had contact with suspected tuberculosis patients. All patients presented chronic occult onset, with an average of 3 (1.75, 5) months. Six cases had local masses, and 13 cases had swelling as the main clinical manifestations. Twelve patients (63.2%) presented manifestations at single sites, and seven patients presented manifestations at multiple sites, including the thigh, calf, arm, chest wall, dorsal, psoas, gluteal, and forehead muscles. Of the 19 total patients, 13 (68.4%) reported pain, and only 8 (42.1%) patients presented tuberculosis symptoms. All patients received laboratory results associated with Mycobacterium tuberculosis infection. Fourteen (73.7%) of the 19 patients underwent skeletal muscle biopsy, where granulomatous inflammation was observed. Eighteen patients were treated with anti-tuberculosis therapies. Sixteen patients improved or recovered after anti-tuberculosis treatment, and unfortunately, two patients died. Conclusion: As a kind of systemic disease, MT is mainly characterized by painful or painless muscle masses and swelling at a single site or at multiple sites. Patients with a history of tuberculosis and immune system disease are susceptible to MT. A diagnosis is mainly made on the basis of the results of pathological biopsy and bacteriological culture. Early diagnosis and timely standardized anti-tuberculosis treatment can improve the prognosis.